Hybrid Algorithms of Nonexpansive Semigroups for Variational Inequalities - Peixia Yang; Yonghong Yao; Yeong-Cheng Liou; Rudong Chen (Journal of Applied Mathematics)
Two hybrid algorithms for the variational inequalities over the common fixed points set of nonexpansive semigroups are presented. Strong convergence results of these two hybrid algorithms have been obtained in Hilbert spaces. The results improve and extend some corresponding results in the literature.